Response of Ethiopian coffee price to the world coffee price: Evidence from dynamic ARDL simulations and nonlinear ARDL cointegration - Shemelis Kebede Hundie; Bane Biratu (Cogent Economics & Finance, 2022)
World coffee prices may have crucial implications on domestic prices of coffee. However, empirical evidence on the effect of world coffee prices on the price of coffee traded at the Ethiopian Commodity Exchange (ECX) is very scant. The main objective of this study is to analyze the response of the price of coffee traded at ECX to change in world coffee price. Monthly time series data ranging from July 2009 to June 2020 were used to address the objectives of this study. The result of the Kapetanios and Shin unit root test shows that majority of the series are stationary at first difference while some variables are stationary at level. The ARDL bounds test was applied to examine whether co-movement exists between the world coffee price and the price of coffee traded at ECX and the result reveals that the two prices are cointegrated. The nonlinear ARDL was applied to test the presence of asymmetric price transmission from the world coffee price to the ECX coffee price. The result reveals that there is an asymmetric price transmission both in the short-run and long-run. ECX coffee prices respond more to a positive shock in world coffee prices than a negative shock in the same variable. Results from the dynamic ARDL simulations reveal that a counterfactual shock in world coffee price has a long-lasting short-and long-term effect on ECX coffee price. The TY and frequency-domain Granger causality test results indicate that all variables except the exchange rate the world coffee price Granger cause ECX coffee price. The frequency-domain Granger causality test results show that world coffee price, economic growth, and money supply granger cause ECX coffee price in the long-run while trade openness and volume of coffee exported granger cause ECX coffee price in the short term. Policymakers should focus on improving competitiveness and transaction cost prevailing in the coffee market in Ethiopia.
Keywords: 330; ECX coffee price; world coffee prices; dynamic ARDL simulations; NARDL; asymmetric price transmission